KNOWLEDGE, ATTITUDES AND PRACTICES OF MEDICAL DOCTORS AND DENTISTS REGARDING MEDICAL ERRORS IN THE HEALTHCARE SYSTEM OF THE REPUBLIC OF NORTH MACEDONIA - Kokolanski, Vlatko; Poposki, Bojan; Spasovski, Spiro; Andonovska, Marija; Ivanovski, Kjiro; Nikolovska, Julijana; Stefkovska, Natasa; Mladenovski, Marko (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: Medical errors represent a major global public health concern with significant implications for patient safety, healthcare quality, and professional accountability, and remain insufficiently studied in transitional healthcare systems such as the Republic of North Macedonia.  Aim of the study: The aim of this study was to evaluate and compare the knowledge, attitudes, and practices of medical doctors and dentists concerning medical errors in the healthcare system of the Republic of North Macedonia.  Material and Methods: A cross-sectional, questionnaire-based study was conducted among 200 licensed clinicians (100 medical doctors and 100 dentists) working in public and private healthcare institutions in Skopje. A structured, anonymous, 14-item questionnaire adapted from validated international instruments was used to assess exposure to information on medical errors, perceptions of error frequency and significance, contributing factors, and self-reported experiences. Data was analyzed using SPSS v24, with group differences evaluated using Chi-square tests (p < 0.05).  Results: Most participants reported encountering medical error information “sometimes” (41.0%, p < 0.05). Medical errors were considered a very significant problem by 53.5% and quite significant by 36.5%. Serious errors were perceived as not very likely in hospital (47.0%) and specialist care (42.0%). Hospital-acquired infections and diagnostic errors were viewed as most likely, while surgical, medication, and device-related errors were judged less probable. Workload and stress (55.0%) and inadequate communication/teamwork (50.0%) were the most frequently cited contributing factors. A total of 19.5% self-reported having committed a medical error, with medical doctors reporting errors nearly twice as often as dentists (26.0% vs. 13.0%, p < 0.05).  Conclusion: Macedonian clinicians acknowledge medical errors as a significant issue yet perceive serious events as relatively infrequent. These findings highlight the need for system-level improvements in teamwork, diagnostic safety, workload management, and a supportive, non-punitive reporting culture. Keywords: medical errors, patient safety, medical doctors, dentists, attitude of health personnel.